Influence of physicians' life stances on attitudes to end-of-life decisions and actual end-of-life decision-making in six countries. Issue 4 (28th March 2008) - Cohen, J; van Delden, J; Mortier, F; Löfmark, R; Norup, M; Cartwright, C; Faisst, K; Canova, C; Onwuteaka-Philipsen, B; Bilsen, J; ,
Abstract : Aim: To examine how physicians' life stances affect their attitudes to end-of-life decisions and their actual end-of-life decision-making. Methods: Practising physicians from various specialties involved in the care of dying patients in Belgium, Denmark, The Netherlands, Sweden, Switzerland and Australia received structured questionnaires on end-of-life care, which included questions about their life stance. Response rates ranged from 53% in Australia to 68% in Denmark. General attitudes, intended behaviour with respect to two hypothetical patients, and actual behaviour were compared between all large life-stance groups in each country. Results: Only small differences in life stance were found in all countries in general attitudes and intended and actual behaviour with regard to various end-of-life decisions. However, with regard to the administration of drugs explicitly intended to hasten the patient's death (PAD), physicians with specific religious affiliations had significantly less accepting attitudes, and less willingness to perform it, than non-religious physicians. They had also actually performed PAD less often. However, in most countries, both Catholics (up to 15.7% in The Netherlands) and Protestants (up to 20.4% in The Netherlands) reported ever having made such a decision. Discussion: The results suggest that religious teachings influence to some extent end-of-life decision-making, but are certainly not blankly accepted by physicians, especially when dealing with real patients and circumstances. Physicians seem to embrace religious belief in a non-imperative way, allowing adaptation to particular situations.